War and Peace in the Hebrew Bible - Hanson, Paul D. (Interpretation, 1984)
If one were to choose a single word to describe the reality for which God created the world, and in which he seeks to sustain the community of those who respond to his initiating grace as an invitation to participate in it, that word would be “shalom.”